Analisis Pengendalian Kualitas Produksi Teh Hitam Celup di Pusat Penelitian Teh dan Kina, Kabupaten Bandung, Jawa Barat - Farasgali, Najma Aulia; Ernah, Ernah; Anggita, Sotya Tresna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Tea is a major plantation commodity that contributes significantly to the national agribusiness sector. One of the tea products currently being developed is Black Tea Bags at the Pusat Penelitian Teh dan Kina (PPTK), Bandung Regency, West Java, which began production in November 2024 and is still in its initial stage. This study aims to analyze the quality control process in the production of Black Tea Bags and to identify the types and causes of product defects. The research used a descriptive qualitative approach with a case study design. Data collection techniques included interviews, participatory observation, documentation, and document analysis, with data analyzed using Statistical Quality Control (SQC) tools such as check sheets, pareto diagrams, control charts, and fishbone diagram. The results show that quality control has not yet been implemented optimally, as evidenced by six out of seven observations falling outside the statistical control limits. Three types of defects were identified: tea bag, thread, and label defects, with tea bag defects being the most dominant. The contributing factors to these defects include human factors, methods, raw materials, machinery and equipment, and the production environment. PPTK is advised to implement scheduled quality control, improve sorting accuracy and defect documentation, and evaluate production machinery, including replacing it with more automated equipment if necessary.